Effeminacy, Masculinity, and Homosocial Bonds: The (Un)Intentional Queering of John Keats - Kimberly, Caroline (Romanticism on the Net)

(untitled) (Université de Montréal, 2004)
AbstractDespite John Keats’s widely acknowledged literary and cultural impact on writers of the Victorian period, little work has been done to explore the biographical methods by which this impact came about. By closely examining the publications and private correspondence of the Keats Circle during the 1820s and 1830s, one can see various patterns to the biographical development of Keats, particularly in relation to their subject’s masculinity. From the widespread eulogies immediately following the poet’s death, to Hunt’s 1828 biographical sketch in Lord Byron and Some of His Contemporaries, to Brown’s 1836 biography manuscript, threads are spun simultaneously of Keats as icon of middle-class masculinity, perpetually youthful Aesthetic ideal, and object of queered desire. Through the complexities of this process, the Keats Circle itself becomes a model of queered male companionship, centred around Keats as a shared object of homosocial affection. The Circle, along with the Cambridge Apostles who would assume control of the biographical project in the 1840s, thereby provide an earlier exemplum of late-Victorian Hellenism than has been previously noted, and establish a crucial conduit for the biographical basis of Keats’s Victorian fame.